Leading Health Indicators 2030: Advancing Health, Equity, and Well-Being - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Beginning in 1979 and in each subsequent decades, the U.S. Department of Health and Human Services (HHS) has overseen the Healthy People initiative to set national goals and objectives for health promotion and disease prevention. At the request of HHS, this study presents a slate of Leading Health Indicators (LHIs) that will serve as options for the Healthy People Federal Interagency Workgroup to consider as they develop the final criteria and set of LHIs for Healthy People 2030.
Keywords: Health and Medicine

Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.
Keywords: Education; Health and Medicine

Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K–12, undergraduate, and graduate and professional levels.
Keywords: Education

Understanding the Well-Being of LGBTQI+ Populations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The increase in prevalence and visibility of sexually gender diverse (SGD) populations illuminates the need for greater understanding of the ways in which current laws, systems, and programs affect their well-being. Individuals who identify as lesbian, gay, bisexual, asexual, transgender, non-binary, queer, or intersex, as well as those who express same-sex or -gender attractions or behaviors, will have experiences across their life course that differ from those of cisgender and heterosexual individuals. Characteristics such as age, race and ethnicity, and geographic location intersect to play a distinct role in the challenges and opportunities SGD people face. Understanding the Well-Being of LGBTQI+ Populations reviews the available evidence and identifies future research needs related to the well-being of SDG populations across the life course. This report focuses on eight domains of well-being; the effects of various laws and the legal system on SGD populations; the effects of various public policies and structural stigma; community and civic engagement; families and social relationships; education, including school climate and level of attainment; economic experiences (e.g., employment, compensation, and housing); physical and mental health; and health care access and gender-affirming interventions. The recommendations of Understanding the Well-Being of LGBTQI+ Populations aim to identify opportunities to advance understanding of how individuals experience sexuality and gender and how sexual orientation, gender identity, and intersex status affect SGD people over the life course.
Keywords: Behavioral and Social Sciences

The State of Anti-Black Racism in the United States: Reflections and Solutions from the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The mission of the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine at the National Academies of Sciences, Engineering, and Medicine is to advance discussions on the barriers and opportunities encountered by Black students and professionals as they navigate the pathways from K-12 and postsecondary education to careers in science, engineering, and medicine (SEM) and highlight promising practices for increasing the representation, retention, and inclusiveness of Black men and Black women in SEM. This proceedings serves as a summary of the presentations and discussions from a capstone workshop, held virtually on December 6 and 7, 2021, to review how anti-Black racism had permeated across the topics covered by the Roundtable over the previous 2 years.
Keywords: Policy for Science and Technology

Building Educational Equity Indicator Systems: A Guidebook for States and School Districts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
How can states and schools use data to support their efforts to improve educational equity? Building Educational Equity Indicator Systems: A Guidebook for States and School Districts, provides information to help state and school district leaders develop ways of tracking educational equity within their preK – 12 systems. The guidebook expands on the indicators of educational equity identified in the 2019 National Academies report, Monitoring Educational Equity, showing education leaders how they can measure educational equity within their states and school districts. Some of the indicators focus on student outcomes, such as kindergarten readiness or educational attainment, while others focus on student access to opportunities and resources, such as effective instruction and rigorous curriculum. Together, the indicators provide a robust picture of the outcomes and opportunities that are central to educational equity from preK through grade 12. For each indicator of educational equity identified in the report, the guidebook describes what leaders should measure and what data to use, provides examples of data collection instruments, and offers considerations and challenges to keep in mind. The guidebook is meant to help education leaders catalogue data they already collect and identify new data sources to help them fill gaps.
Keywords: Education; Behavioral and Social Sciences

Suicide Prevention in Indigenous Communities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Indigenous communities experience higher risks for suicide compared to the general U.S. population, with suicide as the second-leading cause of death among Indigenous children and young adults in North America. To reduce this trend, it is essential for prevention and intervention efforts to build on scientific evidence; cultural and local knowledge; and the best community, family, and institutional practices to reduce risk and increase protection. The Forum on Mental Health and Substance Use Disorders and the Forum for Children's Well-Being at the National Academies of Sciences, Engineering, and Medicine convened a three-part virtual public workshop on April 26, 2022, May 13, 2022, and June 10, 2022, to examine suicide risk and protective factors in Indigenous populations, discuss culturally appropriate and effective suicide prevention policies and programs, explore existing data systems and how data can be used for tracking suicide rates, and consider opportunities for action. This Proceedings highlights presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics - National Academy of Engineering (The National Academies Press, 2012)
On August 8-12, 2010 the National Academy of Engineering (NAE), with funding from the National Science Foundation (NSF), convened the Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics (STEM), following the release of several reports highlighting the educational challenges facing minority males. The NSF recognized the need to gather input from research communities that focus on minority males about how to frame investigations of gender-based factors that impact learning and choice in STEM education (both at the precollege and higher education levels) and the workforce for minority males. There was particular interest in framing a research agenda to study how interactions between minority males and societal and educational systems (both formal and informal) encourage or discourage the young men's interest and persistence in STEM. In addition, NSF hoped to gain community input to inform the parameters of a future NSF research program that could effectively address minority male participation in STEM. The Colloquy was held at the Mt. Washington Conference Center in Baltimore, Maryland, with approximately 40 participants, most of them researchers in education, psychology, sociology, mathematics, and physics. Colloquy on Minority Males in Science, Technology, Engineering, and Mathematics presents a summary of the Colloquy's breakout and plenary discussions, which addressed (a) research questions articulated in the breakout groups together with theories and methodologies to begin to address these questions; and (b) considerations for a potential research solicitation for the NSF, with major areas of inquiry concerning access, participation, and success for minority males in STEM. This report reflects the views of the individuals who participated in the plenary and breakout groups. It has been reviewed in draft form by persons chosen for their diverse perspectives and expertise in accordance with procedures approved by the National Academies' Report Review Committee. The purpose of this independent review is to provide candid and critical comments that will assist the institution in making its published report as sound as possible and to ensure that the report meets institutional standards for quality and objectivity.
Keywords: Engineering and Technology; Education

Educational Pathways for Black Students in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Academic preparation is critical to increase Black representation in Science, Engineering, and Medicine, but so, too, are such interrelated factors as providing mentoring and role models in sufficient numbers, adequately funding school and community support services, and analyzing the intentional and unintentional consequences of a range of policies and practices. To address these issues, the Roundtable on Black Men and Black Women of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on September 2 and 3, 2020. Titled "Educational Pathways for Blacks in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions," the workshop provided a platform to explore challenges and opportunities, beginning in the earliest years of life through K-12 schooling, undergraduate and postgraduate education, and into the workforce. Presenters throughout the workshop provided perspectives from research and from their own experiences to discuss the need for systemic solutions inside and outside of formal education institutions. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

Systemic Inequality in the Airport Industry: Exploring the Racial Divide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
For years, transportation systems, including aviation, have operated within a framework that has resulted in systemic inequality and even overt racism. To address this, airports have begun implementing new organizational dynamics and approaches.TRB's Transportation Insights 1: Systemic Inequality in the Airport Industry: Exploring the Racial Divide provides a summary of an in-person TRB Airport Cooperative Research Program (ACRP) Insight Event. The event identified common manifestations of systemic inequality in an airport setting and the unique challenges airports face as they strive to be more diverse, equitable, and inclusive. Examples of practices undertaken by airports and similar industries are also included. The report will be helpful in fostering communication and collaboration on the topic and help identify areas of future interest and research.
Keywords: Transportation and Infrastructure

Assessing the Environmental Justice Effects of Toll Implementation or Rate Changes: Guidebook and Toolbox - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 860: Assessing the Environmental Justice Effects of Toll Implementation or Rate Changes: Guidebook and Toolbox provides a set of tools to enable analysis and measurement of the impacts of toll pricing, toll payment, toll collection technology, and other aspects of toll implementation and rate changes on low-income and minority populations.The guidebook shows the practitioner when and how to apply the tools in the toolbox through an eight-step process framework corresponding to the typical transportation project planning and development process. The guidebook and toolbox together provide an assessment framework and supporting tools to measure the impacts of tolling on such factors as mobility, access, and household expenditures, as well as tools to engage low-income and minority populations.This report is accompanied by NCHRP Web-Only Document 237: Environmental Justice Analyses When Considering Toll Implementation or Rate Changes—Final Report. This report presents information gathered in the development of the guidebook and the toolbox. This web-only document summarizes the technical research and presents the technical memorandum that documents the literature, existing case studies, resource documents, and other reports compiled.
Keywords: Transportation and Infrastructure

Monitoring Educational Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Disparities in educational attainment among population groups have characterized the United States throughout its history. Education is sometimes characterized as the "great equalizer," but to date, the country has not found ways to successfully address the adverse effects of socioeconomic circumstances, prejudice, and discrimination that suppress performance for some groups. To ensure that the pursuit of equity encompasses both the goals to which the nation aspires for its children and the mechanisms to attain those goals, a revised set of equity indicators is needed. Measures of educational equity often fail to account for the impact of the circumstances in which students live on their academic engagement, academic progress, and educational attainment. Some of the contextual factors that bear on learning include food and housing insecurity, exposure to violence, unsafe neighborhoods, adverse childhood experiences, and exposure to environmental toxins. Consequently, it is difficult to identify when intervention is necessary and how it should function. A revised set of equity indicators should highlight disparities, provide a way to explore potential causes, and point toward possible improvements. Monitoring Educational Equity proposes a system of indicators of educational equity and presents recommendations for implementation. This report also serves as a framework to help policy makers better understand and combat inequity in the United States' education system. Disparities in educational opportunities reinforce, and often amplify, disparities in outcomes throughout people's lives. Thus, it is critical to ensure that all students receive comprehensive supports that level the playing field in order to improve the well-being of underrepresented individuals and the nation.
Keywords: Education; Surveys and Statistics

Promoting the Educational Success of Children and Youth Learning English: Promising Futures - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Educating dual language learners (DLLs) and English learners (ELs) effectively is a national challenge with consequences both for individuals and for American society. Despite their linguistic, cognitive, and social potential, many ELs—who account for more than 9 percent of enrollment in grades K-12 in U.S. schools—are struggling to meet the requirements for academic success, and their prospects for success in postsecondary education and in the workforce are jeopardized as a result. Promoting the Educational Success of Children and Youth Learning English: Promising Futures examines how evidence based on research relevant to the development of DLLs/ELs from birth to age 21 can inform education and health policies and related practices that can result in better educational outcomes. This report makes recommendations for policy, practice, and research and data collection focused on addressing the challenges in caring for and educating DLLs/ELs from birth to grade 12.
Keywords: Education; Behavioral and Social Sciences

Guidelines for the Application of Crossing Solutions at Roundabouts and Channelized Turn Lanes for Pedestrians with Vision Disabilities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Web-Only Document 222: Guidelines for the Application of Crossing Solutions at Roundabouts and Channelized Turn Lanes for Pedestrians with Vision Disabilities provides guidance to engineers and planners on the design of roundabouts and channelized turn lanes for accessibility. NCHRP Web-Only Document 222 is the final report for NCHRP Research Report 834: Crossing Solutions at Roundabouts and Channelized Turn Lanes for Pedestrians with Vision Disabilities: A Guidebook.The accessibility of modern roundabouts and intersections with channelized turn lanes is an important civil rights challenge in the United States that has broad potential implications for engineering practice in this country. This report builds on the results of NCHRP Report 674: Crossing Solutions at Roundabouts and Channelized Turn Lanes for Pedestrians with Vision Disabilities. It provides a framework for empirical study and analysis of accessibility performance, documents field testing of several treatments, and provides a research extension through modeling and simulation to expand the results beyond the field-tested sites.
Keywords: Transportation and Infrastructure

The Science of Effective Mentorship in STEMM - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Mentorship is a catalyst capable of unleashing one's potential for discovery, curiosity, and participation in STEMM and subsequently improving the training environment in which that STEMM potential is fostered. Mentoring relationships provide developmental spaces in which students' STEMM skills are honed and pathways into STEMM fields can be discovered. Because mentorship can be so influential in shaping the future STEMM workforce, its occurrence should not be left to chance or idiosyncratic implementation. There is a gap between what we know about effective mentoring and how it is practiced in higher education. The Science of Effective Mentorship in STEMM studies mentoring programs and practices at the undergraduate and graduate levels. It explores the importance of mentorship, the science of mentoring relationships, mentorship of underrepresented students in STEMM, mentorship structures and behaviors, and institutional cultures that support mentorship. This report and its complementary interactive guide present insights on effective programs and practices that can be adopted and adapted by institutions, departments, and individual faculty members.
Keywords: Education

English Learners in STEM Subjects: Transforming Classrooms, Schools, and Lives - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The imperative that all students, including English learners (ELs), achieve high academic standards and have opportunities to participate in science, technology, engineering, and mathematics (STEM) learning has become even more urgent and complex given shifts in science and mathematics standards. As a group, these students are underrepresented in STEM fields in college and in the workforce at a time when the demand for workers and professionals in STEM fields is unmet and increasing. However, English learners bring a wealth of resources to STEM learning, including knowledge and interest in STEM-related content that is born out of their experiences in their homes and communities, home languages, variation in discourse practices, and, in some cases, experiences with schooling in other countries.
Keywords: Education

Closing the Opportunity Gap for Young Children - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Many young children in the United States are thriving and have access to the conditions and resources they need to grow up healthy. However, a substantial number of young children face more challenging conditions such as: poverty; food insecurity; exposure to violence; and inadequate access to health care, well-funded quality schools, and mental health care. In many cases, the historical origins of unequal access to crucial supports for children's physical, emotional, and cognitive development are rooted in policies that intentionally segregated and limited various populations' access to resources and create opportunity gaps that intertwine and compound to affect academic, health, and economic outcomes over an individual's life course and across generations. Closing the Opportunity Gap for Young Children, identifies and describes the causes, costs, and effects of the opportunity gap in young children and explores how disparities in access to quality educational experiences, health care, and positive developmental experiences from birth through age eight intersect with key academic, health, and economic outcomes. The report identifies drivers of these gaps in three key domains—education, mental health, and physical health—and offers recommendations for policy makers for addressing these gaps so that all children in the United States have the opportunity to thrive. In addition, the report offers a detailed set of recommendations for policy makers, practitioners, community organizations, and philanthropic organizations to reduce opportunity gaps in education, health, and social-emotional development.
Keywords: Behavioral and Social Sciences

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.
Keywords: Education; Policy for Science and Technology; Engineering and Technology; Math, Chemistry, and Physics; Industry and Labor

Addressing Diversity, Equity, Inclusion, and Anti-Racism in 21st Century STEMM Organizations: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Academies of Sciences, Engineering, and Medicine's Committee on Addressing Diversity, Equity, Inclusion, and Anti-Racism in 21st Century STEMM Organizations convened a national summit in July 2021 that highlighted how racism operates at different levels in science, technology, engineering, mathematics, and medicine (STEMM) settings; reviewed policies and practices for confronting systemic racism; and explored ways to advance diversity, equity, and inclusion in STEMM settings. The 2-day, public webcast summit explored the empirical and experiential evidence related to the ways in which systemic racism and other barriers impede STEMM careers for historically marginalized racial/ethnic groups, and explored ways to address these barriers, including strategies undertaken by stakeholder communities. In this summit, speakers discussed how diversity, equity, inclusion, and anti-racism impact STEMM organizations. The workshop presentations focused on issues related to the history of racism in the United States, the lasting legacy of biased policies in the nation, and the research on practices to address systemic and structural racism in STEMM organizations. This publication summarizes the presentation and discussion of summit.
Keywords: Behavioral and Social Sciences

Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Children are the foundation of the United States, and supporting them is a key component of building a successful future. However, millions of children face health inequities that compromise their development, well-being, and long-term outcomes, despite substantial scientific evidence about how those adversities contribute to poor health. Advancements in neurobiological and socio-behavioral science show that critical biological systems develop in the prenatal through early childhood periods, and neurobiological development is extremely responsive to environmental influences during these stages. Consequently, social, economic, cultural, and environmental factors significantly affect a child's health ecosystem and ability to thrive throughout adulthood. Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity builds upon and updates research from Communities in Action: Pathways to Health Equity (2017) and From Neurons to Neighborhoods: The Science of Early Childhood Development (2000). This report provides a brief overview of stressors that affect childhood development and health, a framework for applying current brain and development science to the real world, a roadmap for implementing tailored interventions, and recommendations about improving systems to better align with our understanding of the significant impact of health equity.
Keywords: Health and Medicine; Education